Platelet indices and their correlation with HbA1c and association with microvascular complications in type-2 diabetes mellitus - Sangapur, Shivakanth M.; R. S., Darshan; Sharanabasappa; Meena, Baldev (International Journal of Research in Medical Sciences, 2023)
Background: Depending on the aetiology of the DM, factors contributing to hyperglycaemia include reduced insulin secretion, decreased glucose utilization, and increased glucose production. Mean platelet volume (MPV) and platelet distribution width (PDW) are important, simple, effortless, and cost-effective tools measured by hematology analyser which assess the volume and function of platelets. Analysing the platelet parameters can act as an alarm for progression of complications of DM. Hence, we studied the platelet parameters in diabetic patients with good and poor glycaemic control and their association in microvascular complications. Methods: This study was conducted on 100 patients having diabetes mellitus. All the patients were subjected to detailed history regarding age, sex, occupation, socioeconomic status, GPE and systemic examination. Results: Out of 100 cases, 29 patients had a good glycemic control (HbA1c<7%) and 71 had poor glycemic control (HbA1c>7%). Mean FBS was 118.59±19.36 mg/dl in good control group and 158.79±29.21 mg/dl in poor control (p<0.001). Mean PPBS was 159.86±37.78 mg/dl in good control group and 235.80±53.28 mg/dl in poor control group (p<0.001). Good glycemic control group had mean MPV of 7.89±0.63 fl and poor glycemic control group had mean MPV 10.06 fl (p<0.001). Mean PDW was 12.32±1.94 in good control group and 13.81±2.25 in poor control group. Conclusions: Our study indicates that MPV and PDW are increased in diabetic patients, more so in patients with microvascular complications than in those without complications. Hence, they can be used as markers in predicting the microvascular complications in diabetes mellitus.